Transfusion Related Emergencies - Megan Boysen Osborn; Min-Ha Tran (eScholarship Publishing, University of California, 2016)
Audience: This exercise is appropriate for all emergency medicine learners (residents and medical students) and learners from other specialties (internal medicine, family medicine, anesthesia). Introduction: About 85 million red blood cell units are transfused worldwide each year. Transfusion reactions can complicate up to 8% of blood transfusions and can range from benign to life threatening. An emergency physician must be able to discuss the risks and benefits of blood transfusion with patients, as well as manage the associated complications of blood transfusion. Objectives: At the end of this didactic session, the learner will be able to: 1) list the various transfusion reactions and their approximate incidence; 2) understand the pathophysiology behind each transfusion reaction; 3) describe the management for each type of transfusion reaction; and 4) discuss the plan for prevention of future transfusion reactions. Method: This is a classic team based learning exercise (cTBL).